PROBLEMATIKA POLITIK SEKTARIANISME DI LEBANON DAN DINAMIKA POLITIK REGIONAL - Kartini , Indriana (Tashwirul Afkar, 2024)
Lebanon has faced sectarian problem in its political, economics, social, and cultural life. Confessionalism system that become its national identity has made difficulties for the country to escape from sectarianism problem. Lebanon constitution has ordained confessionalism system by acknowledging many religious sects in the country. This system is hoped to answer the question of cultural and political identity of Lebanon. However, there are differences between Muslim and Christian communities in viewing nationality of Lebanon. Muslim elites identify themself with Arab nationalism and inspired by establishing national sovereignty in unification with Syria. While Christians inspired by Lebanon sovereignty through Lebanon-Phoenicia identity and Western face. This article will examine problematics of sectarianism politics in Lebanon by analysing the relations between political Islam and other power (Christians) in the country. This article will also examine the regional and international political dynamics that influencing Lebanese politics